Necrotizing fasciitis of the hand: a case report - Minini, Andrea; Galli, Stefano; Salvi, Andrea Giordano; Zarattini, Guido (Acta Biomedica Atenei Parmensis, 2018)
Necrotizing Fasciitis is a rare life-threatening infection , usually polymicrobial, that frequently affects the extremities in as many as two thirds of the cases. It typically involves primarily the muscular fascia, and then spreads through muscular and subcutaneous tissues. The early diagnosis may be challenging , and appears to be crucial in the management of this condition. We report a case of a 45-year-old man, former drug abuser, diabetic, HCV +,  who developed a necrotizing fasciitis of the hand following a minor trauma. Early diagnosis based on clinical, laboratory (LRINEC score) and radiological findings, together with an accurate debridement of the affected site, allowed us to limitate the amputation to the third ray only. The reconstruction with the capitate osteotomy and the coverage with the posterior interosseous flap helped us in further reduction of the functional impairment of the hand.